2017
DOI: 10.7554/elife.21221
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological targeting of the transcription factor SOX18 delays breast cancer in mice

Abstract: Pharmacological targeting of transcription factors holds great promise for the development of new therapeutics, but strategies based on blockade of DNA binding, nuclear shuttling, or individual protein partner recruitment have yielded limited success to date. Transcription factors typically engage in complex interaction networks, likely masking the effects of specifically inhibiting single protein-protein interactions. Here, we used a combination of genomic, proteomic and biophysical methods to discover a suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 48 publications
(67 reference statements)
4
76
0
Order By: Relevance
“…Pharmacological inhibition of TFs (see above for AP-1), signal transduction molecules, such as kinases or acetylases that converge in the activation of TFs, could represent a viable approach for manipulating the senescent phenotype in vivo 59 . Alternatively, small molecules that prevent TF-TF combinatorial interactions could also be envisioned 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of TFs (see above for AP-1), signal transduction molecules, such as kinases or acetylases that converge in the activation of TFs, could represent a viable approach for manipulating the senescent phenotype in vivo 59 . Alternatively, small molecules that prevent TF-TF combinatorial interactions could also be envisioned 60 .…”
Section: Discussionmentioning
confidence: 99%
“…SOX18 homo- and heterodimerization can be inhibited by a small molecule, SM4 2022 and by an FDA-approved beta blocker, propranolol 23 . Propranolol is produced as a 1:1 racemic mixture of R(+) and S(-) enantiomers.…”
Section: Resultsmentioning
confidence: 99%
“…As SOX18 TF functionality is dependent on or modulated by the presence of other co-binders, targeting of this GRN was an attractive anti-angiogenic strategy. The first step was to identify co-binders of SOX18 using ChIP-MS as a first line of screening [128]. These data have been coupled with a validation by AlphaScreen and single molecule fluorescence approaches that were optimised to scrutinise pairwise protein interactions in high throughput.…”
Section: Sox18mentioning
confidence: 99%
“…After identifying potential drug targets, Overman et al [128] screened a structurally diverse marine extract library for compounds that could interfere with SOX18-DNA interaction, using a fluorescence polarisation assay. From this screen, the authors identified the chemical space that was conserved between multiple compound hits.…”
Section: Sox18mentioning
confidence: 99%
See 1 more Smart Citation